Persistence of a reef fish metapopulation via network connectivity: theory and data. (22nd March 2021) - Dedrick, Allison G.; Catalano, Katrina A.; Stuart, Michelle R.; White, J. Wilson; Montes, Humberto R.; Pinsky, Malin L.
Abstract: Determining metapopulation persistence requires understanding both demographic rates and patch connectivity. Persistence is well understood in theory but has proved challenging to test empirically for marine and other species with high connectivity that precludes classic colonisation–extinction dynamics. Here, we assessed persistence for a yellowtail anemonefish ( Amphiprion clarkii ) metapopulation using 7 years of annual sampling data along 30 km of coastline. We carefully accounted for uncertainty in demographic rates. Despite stable population abundances through time and sufficient production of surviving offspring for replacement, the pattern of connectivity made the metapopulation unlikely to persist in isolation and reliant on immigrants from outside habitat. To persist in isolation, the metapopulation would need higher fecundity or to retain essentially all recruits produced. This assessment of persistence in a marine metapopulation shows that stable abundance alone does not indicate persistence, emphasising the necessity of assessing both demographic and connectivity processes to understand metapopulation dynamics. Abstract : We assessed persistence for a yellowtail anemonefish ( Amphiprion clarkii ) metapopulation using seven years of annual sampling data along 30 km of coastline. Despite stable population abundances through time and sufficient production of surviving offspring for replacement, the pattern of connectivity made the metapopulation unlikely to persist in isolation and reliant on immigrants from outside habitat. This assessment of persistence in a marine metapopulation shows that stable abundance alone does not indicate persistence, emphasizing the necessity of assessing both demographic and connectivity processes to understand metapopulation dynamics.